Lithium iron phosphate positive electrode material, preparation method thereof and lithium battery

By forming a carbon cladding layer on the surface of the lithium iron phosphate positive electrode material and performing particle size grading, the pressing index and particle motion ability of the material are improved, and the problem of low tap density and compaction density of existing materials is solved, and a lithium battery with high energy density and good circulation performance is achieved.

CN119890280AActive Publication Date: 2025-04-25GUANGDONG BRUNP RECYCLING TECH CO LTD

Patent Information

Application Number
CN202510376785.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode materials have low tap density and compaction density, which affects the energy density and cycling performance of the battery.

Method used

By forming a carbon cladding layer on the surface of lithium iron phosphate active material and improving the compression index and particle movement ability of lithium iron phosphate positive electrode material through specific particle size grading and preparation methods, thereby improving its compaction density and cycling performance.

Benefits of technology

The high compaction density and good circulation performance of lithium iron phosphate positive electrode material are achieved, and the energy density and capacity retention rate of lithium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890280A_ABST
    Figure CN119890280A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium battery, and relates to the technical field of lithium ion batteries. According to the method, the pressing index of the lithium iron phosphate positive electrode material is tested by adopting a specific method, so that the pressing index meets a specific range, meanwhile, the average circularity of larger particles in a Dv50-Dv100 range meets a proper range, the lithium iron phosphate positive electrode material has better particle movement capability, and the particles can move at a higher speed to be rearranged during pressing, so that the particle size of the lithium iron phosphate positive electrode material is reduced, and the quality of the lithium iron phosphate positive electrode material is improved. Therefore, the positive pole piece with high compaction density can be obtained, the charge-discharge capacity of the battery can be improved, and meanwhile, the particles can be prevented from being broken when being pressed, so that the positive pole piece has good anti-pressure capability. By adopting the lithium iron phosphate positive electrode material provided by the invention, the lithium battery has relatively high energy density and capacity retention ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium battery. Background Art

[0002] Lithium iron phosphate is one of the most competitive cathode active materials for lithium-ion batteries on the market. Compared with lithium cobalt oxide and ternary cathode materials, it has a longer life and better safety performance. In addition, lithium iron phosphate has a 170mAh g -1 Theoretical specific capacity and platform discharge voltage of 3.4V make it have considerable energy density.

[0003] Tap density and compaction density (collectively referred to as bulk density) are important indicators for evaluating positive electrode materials. Tap density refers to the bulk density of powder materials after being tapped, and compaction density refers to the bulk density of powder materials after being stabilized under pressure. Therefore, both reflect the mass of positive electrode materials contained in a unit volume, which will directly affect the compaction density of the prepared electrode sheet, thereby affecting the energy density of the battery. Due to its crystal structure, lithium iron phosphate positive electrode materials have a low ion diffusion rate and conductivity. The existing technology usually uses a large and small particle grading method to improve the tap density and compaction density of lithium iron phosphate positive electrode materials, so that it can take into account good bulk density and Li + Diffusion rate. However, the tap density and compaction density of the positive electrode material are not limited to the particle size distribution, but are also affected by many other factors.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium battery, aiming to provide a lithium iron phosphate positive electrode material with high compaction density and good cycle performance.

[0006] The present invention is achieved in that: In a first aspect, the present invention provides a lithium iron phosphate positive electrode material, comprising a lithium iron phosphate active material, wherein a carbon coating layer is provided on the surface of the lithium iron phosphate active material; The average circularity of the particles of lithium iron phosphate positive electrode material within the range of Dv50-Dv100 is greater than or equal to 0.6; Compression index of lithium iron phosphate cathode material The compression index is 0.4-5.0, wherein the compression index is obtained by the following method: The density-pressure relationship curve of the lithium iron phosphate positive electrode material at different pressing speeds was obtained, and a linear fit was performed on the portion of the density-pressure relationship curve above 100 MPa to obtain the corresponding slope, and a curve of the relationship between the pressing speed and the slope was drawn. The slope of the fitting line obtained by linear fitting of the curve of the relationship between the pressing speed and the slope was the pressing index.

[0007] In an optional embodiment, the particle strength of the lithium iron phosphate positive electrode material is 40 MPa-150 MPa.

[0008] In an optional embodiment, the lithium iron phosphate positive electrode material satisfies at least one of the following characteristics: Feature A1: Particle strength is 60MPa-120MPa; Feature A2: The average circularity of particles in the range of Dv50-Dv100 is 0.65-0.80; Feature A3: compacted density is 1.5g / cm 3 -3.0g / cm 3 ; Feature A4: The mass proportion of the carbon coating layer in the lithium iron phosphate positive electrode material is 0.5%-5%.

[0009] In an optional embodiment, define: compressibility factor = ; The lithium iron phosphate positive electrode material meets the compressibility factor of 120MPa-300MPa.

[0010] In a second aspect, the present invention provides a method for preparing a lithium iron phosphate positive electrode material according to any one of the aforementioned embodiments, comprising: mixing iron phosphate and a polymer solution containing lithium ions, and then mixing with a curing agent for curing reaction to obtain a gel; wherein the polymer solution containing lithium ions is obtained by dissolving a soluble lithium salt and a polymer in a solvent; The gel is crushed and then dried to obtain a precursor; calcining the precursor to prepare carbon-coated lithium iron phosphate; Carbon-coated lithium iron phosphate with different particle sizes is mixed.

[0011] In an optional embodiment, the process of preparing the gel has at least one of the following characteristics: Feature B1: The polymer is a soluble polymer containing at least one of a hydroxyl group, a vinyl group and an epoxy group; the curing agent is selected according to the active groups contained in the polymer. When the polymer contains a hydroxyl group, the curing agent is a glycidyl ether; when the polymer contains a vinyl group, the curing agent is a soluble photoinitiator; when the polymer contains an epoxy group, the curing agent is a polyol; Feature B2: The soluble lithium salt is selected from at least one of lithium chloride, lithium hydroxide, lithium acetate and lithium oxalate; Feature B3: The solvent is selected from at least one of water, ethanol, methanol and isopropanol; Feature B4: The concentration of lithium ions in the lithium ion-containing polymer solution is 0.2M-0.8M, the mass percentage of the polymer in the lithium ion-containing polymer solution is 1%-3%, and the mass ratio of the added amount of the curing agent to the polymer is (1-5): 100; Feature B5: After mixing anhydrous ferric phosphate, a dopant and a polymer solution containing lithium ions, the mixture is mixed with a curing agent for a curing reaction, wherein the dopant is a soluble compound containing a doping element, and the doping element is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn, Y, Mg, Na, N, S and F; the molar ratio of the total molar amount of the iron element and the doping element in the anhydrous ferric phosphate to the lithium element is controlled to be 1: (1.01-1.10); Feature B6: The curing reaction method is selected from at least one of heating stirring reaction, ultraviolet irradiation stirring reaction and microwave irradiation stirring reaction; when the curing reaction is carried out by heating stirring reaction, the reaction temperature is controlled to be 50°C-80°C; when the curing reaction is carried out by ultraviolet irradiation stirring reaction, the light wavelength is controlled to be 200nm-400nm; when the curing reaction is carried out by microwave irradiation stirring reaction, the microwave irradiation power is controlled to be 200W-500W; Feature B7: The solid content of the prepared gel is 30%-50%.

[0012] In an optional embodiment, the gel is crushed and then fluidized dried; Among them, fluidized drying refers to placing the crushed gel in a fluidized bed for drying, controlling the drying temperature to 80°C-120°C, and the air flow rate to 50mL / min-400mL / min.

[0013] In an optional embodiment, the process of preparing carbon-coated lithium iron phosphate from a precursor has at least one of the following characteristics: Characteristic C1: calcination temperature is 550°C-650°C, and calcination time is 2h-6h; Characteristic C2: Calcination is carried out under an inert atmosphere; Feature C3: The precursor enters the flash dryer for preheating before calcination, and the inlet air temperature of the flash dryer is controlled to be 300°C-500°C, the outlet air temperature is 100°C-150°C, the rotation speed is 10Hz-30Hz, and the feed frequency is 10Hz-30Hz; Feature C4: After the precursor is calcined, it is crushed and demagnetized to obtain carbon-coated lithium iron phosphate.

[0014] In an optional embodiment, the method of mixing carbon-coated lithium iron phosphate with different particle sizes is selected from the first method or the second method; The process of using the first method for proportioning includes: mixing two carbon-coated lithium iron phosphates with different particle size distributions in proportion, and the Dv50 of the two carbon-coated lithium iron phosphates with different particle size ranges are Dv50 and Dv50, respectively. a 、Dv50 b , where 15μm≥Dv50 a ≥2.4Dv50 b ≥1μm; with Dv50 a and Dv50 b The mass ratio of the two carbon-coated lithium iron phosphates is (20%~35%): (65%~80%); The process of using the second method for proportioning includes: mixing three carbon-coated lithium iron phosphates with different particle size distributions in proportion, and the Dv50 of the three carbon-coated lithium iron phosphates with different particle size ranges are Dv50 and Dv50, respectively. a 、Dv50 b 、Dv50 c , where 15μm≥Dv50 a ≥2.4Dv50 b ≥2.4 2 Dv50 c ≥2μm; with Dv50 a 、Dv50 b and Dv50 c The mass ratios of the three types of carbon-coated lithium iron phosphate are (2%~20%): (40%~60%): (30%~40%).

[0015] In a third aspect, the present invention provides a lithium battery, comprising the lithium iron phosphate positive electrode material of any one of the aforementioned embodiments or the lithium iron phosphate positive electrode material prepared by any one of the preparation methods of the aforementioned embodiments.

[0016] The present invention has the following beneficial effects: The present invention adopts a specific method to test the compression index of lithium iron phosphate positive electrode material , so that the compression index meets a specific range, and the average circularity of the larger particles in the range of Dv50-Dv100 meets an appropriate range, such lithium iron phosphate positive electrode material has better particle movement ability, and the particles can move and rearrange at a faster speed during compression, which is conducive to obtaining a positive electrode sheet with high compaction density and improving the charge and discharge capacity of the battery, and is also conducive to avoiding the particles from breaking when under pressure, so that it has good compression resistance. The lithium iron phosphate positive electrode material provided by the present invention can make the lithium battery have both high energy density and capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 It is the density-pressure relationship curve; Figure 2 for Figure 1 Schematic diagram after curve fitting; Figure 3 It is a curve diagram of the relationship between pressing speed and slope; Figure 4 TEM test images of Comparative Example 1 and Example 3; Figure 5 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1; Figure 6 This is the SEM image of the lithium iron phosphate positive electrode material prepared in Example 3. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0020] An embodiment of the present invention provides a lithium iron phosphate positive electrode material, including a lithium iron phosphate active material, and a carbon coating layer is provided on the surface of the lithium iron phosphate active material to form a carbon-coated lithium iron phosphate positive electrode material.

[0021] The average circularity of particles in the range of Dv50-Dv100 of the lithium iron phosphate positive electrode material provided in an embodiment of the present invention is greater than or equal to 0.6. The particles in this range are relatively large and have a greater impact on the overall movement ability of the powder material. The average circularity of these particles can be 0.60, 0.65, 0.70, 0.80, 0.90, 1.00, etc.

[0022] The present invention creatively defines the compression index of lithium iron phosphate positive electrode material , and the compression index is controlled to be 0.4-5.0, such as 0.40, 0.50, 0.80, 1.00, 1.50, 2.00, 2.50, 3.00, 3.50, 4.00, 4.50, 5.00, etc. The compression index is obtained by the following method: obtaining the density-pressure relationship curve of the lithium iron phosphate positive electrode material at different compression speeds, and performing linear fitting on the portion of the density-pressure relationship curve above 100 MPa (the linear growth portion is usually above 100 MPa) (the goodness of fit r is required to be 0.5). 2 ≥0.99) and obtain the corresponding slope, draw a curve of the relationship between the pressing speed and the slope, and perform a linear fit on the curve of the relationship between the pressing speed and the slope (requires a goodness of fit r 2 ≥0.98) The slope of the fitting line is the compression index. For the specific test method, refer to GB / T 11106-2022 "Method for Determining the Compression Strength of Cylindrical Compacts for Metal Powders", and then use Origin and other software to fit the external tangent line of the relationship curve. Compression Index It reflects the growth rate of the pressure growth rate of the lithium iron phosphate positive electrode material at different pressing speeds, and reflects the activity of the lithium iron phosphate positive electrode material particles.

[0023] It should be noted that the pressure growth rate of powder materials is inconsistent at different pressing speeds. The faster the pressing speed, the faster the pressure growth rate. The reason is that when pressure is applied, the powder particles dissipate pressure by movement and rearrangement, but if the pressing speed is too fast, the stress is difficult to dissipate quickly, resulting in a rapid increase in pressure. Therefore, the movement ability of the powder particles has an impact on their pressure dissipation ability. The movement ability of the particles, that is, the quality of the stress dissipation ability, will directly affect its tap density or compaction density, thereby affecting the energy density of the battery; furthermore, it will directly affect the stability of the positive electrode material during the cycle process, thereby affecting the cycle life and safety. Through a large number of experiments, the present invention found that the particle movement ability of the lithium iron phosphate positive electrode material is related to its particle size distribution, particle morphology, and particle surface properties. Specifically, when the lithium iron phosphate positive electrode material particles have a good particle size grading effect, the particles only need to move through a shorter path to complete the filling of pores to dissipate stress, so the mobility is higher; when the lithium iron phosphate positive electrode material particles have a higher roundness, the contact area between the particles is the lowest and the relative mobility is higher, so the mobility is higher; when the carbon coating layer of the lithium iron phosphate positive electrode material particles is more uniform, the friction between the particles is smaller, so the relative mobility is higher.

[0024] The embodiment of the present invention provides a compression index Lithium iron phosphate cathode materials with a compression index of 0.4 to 5 have better particle movement ability. When pressed, the particles can move and rearrange at a faster speed, which is conducive to obtaining a positive electrode sheet with a high compaction density to improve the battery's charge and discharge capacity, and at the same time helps to avoid particle breakage when pressed. Generally speaking, the broken particles may not be able to maintain the original conductive network structure, making the electron conduction path tortuous, increasing the internal resistance, and affecting the battery's high current discharge performance and efficiency. Usually, the compression index is 0.4 to 5. The smaller it is, the better the particle's mobility.

[0025] In some embodiments, the particle circularity of the lithium iron phosphate positive electrode material is 0.5-1.0, such as 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc.

[0026] In some embodiments, the particle strength of the lithium iron phosphate positive electrode material is 40MPa-150MPa, such as 40MPa, 50MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, 110MPa, 120MPa, 130MPa, 140MPa, 150MPa, etc. When the lithium iron phosphate positive electrode material has a compression index When the particle strength is 40-150MPa and the lithium iron phosphate positive electrode material has good particle mobility and high particle mechanical strength, it is not easy to break when under pressure. Therefore, the lithium iron phosphate positive electrode material has a high compaction density. The positive electrode sheet containing the lithium iron phosphate positive electrode material has a high compaction density and a low internal resistance. The battery containing the positive electrode sheet has good charge and discharge capacity and cycle stability.

[0027] In a preferred embodiment, the particle strength of the lithium iron phosphate positive electrode material is 60MPa-120MPa, and the average circularity of the particles in the range of Dv50-Dv100 is 0.65-0.80. The strength and average circularity of the lithium iron phosphate positive electrode material particles are preferably within the above range, which is conducive to further improving the movement ability of the material and improving the compaction density of the material. The compaction density (test condition is 3T) is 1.5g / cm 3 -3.0g / cm 3 , such as 1.5g / cm 3 , 2.0g / cm 3 , 2.5g / cm 3 、3.0g / cm 3 The mass proportion of the carbon coating layer in the lithium iron phosphate positive electrode material is 0.5%-5%, such as 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, etc.

[0028] Further, define: compressibility factor = The lithium iron phosphate positive electrode material satisfies a compressibility factor of 120MPa-300MPa, such as 120MPa, 150MPa, 180MPa, 200MPa, 230MPa, 250MPa, 300MPa, etc. The larger the compressibility factor, the stronger the compressive resistance of the lithium iron phosphate positive electrode material, and the higher the compaction density of the obtained positive electrode sheet, so the battery capacity is higher and the cycle stability is better.

[0029] The embodiment of the present invention also provides a method for preparing a lithium iron phosphate positive electrode material, combining a sol-gel method and a carbothermal reduction method to prepare a carbon-coated lithium iron phosphate having a uniform carbon coating layer and high circularity, and further preparing a lithium iron phosphate positive electrode material by particle size ratio. The steps are as follows: S1. Preparation of gel A soluble lithium salt and a polymer are dissolved in the same solvent to obtain a polymer solution containing lithium ions. Iron phosphate (such as anhydrous iron phosphate) and the polymer solution containing lithium ions are mixed, and then mixed with a curing agent for a curing reaction to obtain a gel.

[0030] It should be noted that, by dispersing anhydrous ferric phosphate in a polymer solution containing lithium ions to achieve mixing of anhydrous ferric phosphate and lithium ions, and slowly cross-linking the polymer under stirring conditions to form a gel, the amount of iron phosphate, lithium ions and polymer contained in a unit volume is fixed, which is beneficial to the preparation of lithium iron phosphate with uniform shape and similar surface properties, thereby improving the uniformity of the product and reducing resistance; at the same time, the polymer, as a carbon source during subsequent calcination, is evenly coated on the surface of the iron phosphate solid, which is not only beneficial to the formation of a uniform carbon coating layer, but also beneficial to improving the roundness of the obtained lithium iron phosphate.

[0031] In some embodiments, the soluble lithium salt is selected from at least one of lithium chloride, lithium hydroxide, lithium acetate, and lithium oxalate, and the soluble lithium salt may be any one or more of the above. The solvent is selected from at least one of water, ethanol, methanol, and isopropanol, and the solvent may be any one or more of the above.

[0032] In some embodiments, the polymer is a soluble polymer containing at least one of hydroxyl, vinyl and epoxy groups, and the polymer contains any one or more of the above active groups. The curing agent is selected according to the active groups contained in the polymer. When the polymer contains hydroxyl groups, the curing agent is a glycidyl ether, such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, etc.; when the polymer contains vinyl, the curing agent is a soluble photoinitiator, such as photoinitiator 2959, but not limited to this; when the polymer contains epoxy groups, the curing agent is a polyol (such as ethylene glycol, glycerol, etc.), and the preparation of the gel is achieved by reacting the polyol and epoxy groups.

[0033] Specifically, the polymer may be hyaluronic acid, vinyl grafted hydroxymethyl cellulose, agar, guar gum, alginic acid, aliphatic epoxy resin, and the like.

[0034] Furthermore, the concentration of lithium ions in the lithium ion-containing polymer solution is 0.2M-0.8M, such as 0.2M, 0.3M, 0.4M, 0.5M, 0.6M, 0.7M, 0.8M, etc. The mass percentage of the polymer in the lithium ion-containing polymer solution is 1%-3%, such as 1%, 2%, 3%, etc. The amount of the curing agent is determined according to the amount of the polymer, and the mass ratio of the added amount of the curing agent to the polymer is controlled to be (1-5):100, such as 1:100, 2:100, 3:100, 4:100, 5:100, etc.

[0035] In some embodiments, the curing reaction is selected from at least one of heating and stirring reaction, ultraviolet irradiation and stirring reaction, and the curing reaction can be any one or more of the above, which can be selected according to the type of polymer. When the curing reaction is carried out by heating and stirring reaction, the reaction temperature is controlled to be 50°C-80°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc. When the curing reaction is carried out by ultraviolet irradiation and stirring reaction, the light wavelength is controlled to be 200nm-400nm, such as 200nm, 250nm, 300nm, 350nm, 400nm, etc.; when the curing reaction is carried out by microwave irradiation and stirring reaction, the power of microwave irradiation is controlled to be 200W-500W, such as 200w, 300w, 400w, 500w, etc. The solid content of the prepared gel is 30%-50% by adjusting the reaction time, such as 30%, 35%, 40%, 45%, 50%, etc.

[0036] In some embodiments, the doping element is introduced into the gel, and the anhydrous iron phosphate, the dopant and the polymer solution containing lithium ions are mixed, stirred and dispersed evenly, and then the curing agent is added while stirring, and the curing reaction is carried out after the addition is completed. Wherein, the dopant is a soluble compound containing the doping element, and the doping element is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn, Y, Mg, Na, N, S and F, and the doping element can be any one or more of the above. The molar ratio of the total molar amount of the iron element and the doping element in the anhydrous iron phosphate to the lithium element is controlled to be 1: (1.01-1.10), such as 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.10, etc.

[0037] S2, crushing, drying The gel is broken into pieces and then dried to remove impurities such as surface solvents to obtain a precursor.

[0038] In some embodiments, the crushing method can be screening, rolling, grinding, etc. to prevent particle agglomeration.

[0039] In some embodiments, a fluidized bed can be used for fluidized drying to avoid agglomeration. Fluidized drying refers to placing the crushed gel in a fluidized bed for drying, controlling the drying temperature to 80°C-120°C, and the air flow rate to 50mL / min-400mL / min, to obtain precursor particles with a relatively uniform particle size. Specifically, the drying temperature can be 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the air flow rate can be 50mL / min, 100mL / min, 200mL / min, 300mL / min, 400mL / min, etc.

[0040] S3. Calcination The precursor is calcined and the polymer is carbonized to prepare carbon-coated lithium iron phosphate.

[0041] In some embodiments, the calcination temperature is controlled to be 550°C-650°C, such as 550°C, 580°C, 600°C, 630°C, 650°C, etc.; the calcination time is 2h-6h, such as 2h, 3h, 4h, 5h, 6h, etc. The calcination process can be carried out under an inert atmosphere, and the inert atmosphere can be nitrogen, argon, etc.

[0042] In some embodiments, the precursor enters a flash dryer for preheating before calcination, and the air inlet temperature of the flash dryer is controlled to be 300°C-500°C, the air outlet temperature is 100°C-150°C, the rotation speed is 10Hz-30Hz, and the feed frequency is 10Hz-30Hz. Pre-calcination using a flash dryer is conducive to rapid shrinkage of the particles at high temperatures, improving the bonding strength inside the material particles, and thereby improving the mechanical strength characteristics of the material.

[0043] In some embodiments, after the precursor is calcined, it is crushed and demagnetized to obtain carbon-coated lithium iron phosphate. The calcined agglomerated particles are dispersed by crushing, and the magnetic impurities are removed by demagnetization.

[0044] S4, particle size gradation Carbon-coated lithium iron phosphate with different particle sizes is mixed and the grading effect of the lithium iron phosphate positive electrode material is improved through the grading method, which is beneficial to improving its tap density and compaction density, and further beneficial to improving the capacity of the battery.

[0045] In some embodiments, the method of proportioning carbon-coated lithium iron phosphate with different particle sizes is selected from the first method or the second method. The first method is to use two carbon-coated lithium iron phosphates with different particle size distributions for grading, and the second method is to use three carbon-coated lithium iron phosphates with different particle size distributions for grading.

[0046] Further, the process of using the first method to mix the two carbon-coated lithium iron phosphates with different particle size distributions is mixed in proportion, and the Dv50 of the two carbon-coated lithium iron phosphates with different particle size ranges is Dv50 respectively. a 、Dv50 b , where 15μm≥Dv50 a ≥2.4Dv50 b ≥1μm, that is, Dv50 of large particles a Greater than or equal to 2.4 times Dv50 for small particles b , and Dv50 a and 2.4 times Dv50 b The values ​​of are all between 1μm and 15μm, such as 1μm, 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, etc. a and Dv50 b The mass ratio of the two types of carbon-coated lithium iron phosphate is (20%~35%):(65%~80%), and the mass ratio of large-particle carbon-coated lithium iron phosphate and small-particle carbon-coated lithium iron phosphate can be 20%:80%, 25%:75%, 30%:70%, 35%:65%, etc.

[0047] The process of using the second method for proportioning includes: mixing three carbon-coated lithium iron phosphates with different particle size distributions in proportion, and the Dv50 of the carbon-coated lithium iron phosphates with three different particle size ranges of large particles, medium particles and small particles are Dv50 and Dv50, respectively. a 、Dv50 b 、Dv50 c , where 15μm≥Dv50 a ≥2.4Dv50 b ≥2.4 2 Dv50 c ≥2μm, that is, Dv50 of large particles a Greater than or equal to 2.4 times Dv50 of medium particles b , also greater than or equal to 2.4 for small particles 2 Times Dv50 c , and Dv50 a and 2.4 times Dv50 b , 2.4 2 Times Dv50 cThe values ​​of are all between 2μm and 15μm, such as 2μm, 5μm, 8μm, 10μm, 13μm, 15μm, etc. a 、Dv50 b and Dv50 c The mass ratio of large particles, medium particles and small particles of carbon-coated lithium iron phosphate is (2%~20%): (40%~60%): (30%~40%), such as 2%:60%:38%, 5%:55%:40%, 8%:57%:35%, 10%:53%:37%, 13%:57%:30%, 15%:45%:40%, 18%:43%:39%, 20%:40%:40%, etc.

[0048] The embodiment of the present invention also provides a lithium battery positive electrode plate, including the lithium iron phosphate positive electrode material provided by the embodiment of the present invention, which can improve the compaction density of the positive electrode plate. The lithium battery positive electrode plate can also include a positive electrode current collector, a positive electrode active coating is formed on at least one surface of the positive electrode current collector, and the lithium iron phosphate positive electrode material is present in the positive electrode active coating as a positive electrode active material.

[0049] The embodiment of the present invention also provides a lithium battery, including the positive electrode plate of the lithium battery provided by the embodiment of the present invention, which can improve the charge and discharge capacity of the battery. The lithium battery can also include a negative electrode plate, an electrolyte, a diaphragm, etc. to form a complete battery structure, and the specific types of the negative electrode plate, the electrolyte, and the diaphragm are not limited. During the charge and discharge process of the lithium battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate.

[0050] The embodiment of the present invention also provides a device, including the above-mentioned lithium battery (secondary battery), battery module or battery pack, the secondary battery, battery module or battery pack can be used as a power source of the device, and can also be used as an energy storage unit of the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0051] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0052] The present invention provides a lithium iron phosphate positive electrode material as shown in Table 1, and uses the lithium iron phosphate positive electrode material to prepare a positive electrode pole piece and a battery, and tests the pole piece and battery performance, as shown in Table 2.

[0053] Performance test methods and conditions: Electrode sheet resistance: Use Yuanneng Technology BER2100 multi-function electrode sheet resistance meter to test 10 different positions and calculate the average value.

[0054] Tap density: measured in accordance with GB / T30835-2014.

[0055] Compacted density of positive electrode material: The compacted density of positive electrode material is measured in accordance with GB / T30835-2014.

[0056] Compression index: Load 1±0.01g of lithium iron phosphate cathode material into a steel mold, and use the Xinsansi CMT5000 universal mechanical testing machine to continuously compress the powder in the steel mold. The moving speed of the pressure head (compression speed) is selected from any at least 3 speeds of 0.2~15mm / min, for example, 0.2mm / min, 1mm / min, 10mm / min, and 15mm / min respectively. The mechanical testing machine automatically records the pressure and displacement of the beam during the compression process, and according to the specifications of the steel mold and the mass of the powder Calculate the powder density and pressure, and obtain the relationship curve between the powder density and pressure at different pressing speeds. Perform a linear fit on the linear growth part of the density-pressure relationship curve (usually when the pressure is above 100 MPa) (requires the goodness of fit r2 ≥ 0.99) and obtain the corresponding slope 1. Each sample is measured at least three times at each speed to obtain the average value of slope 1. Then draw a relationship curve between the pressing speed and the average value of slope 1. The slope 2 obtained by linear fitting the relationship curve between the pressing speed and the average value of slope 1 is the pressing index, and the goodness of fit r 2 ≥0.98 is valid data. The test method refers to GB / T 11106-2022 "Method for Determining the Strength of Cylindrical Compacts for Metal Powders by Compression", and the relationship curve is linearly fitted using software such as Origin. Before linear fitting of the relationship curve between density and pressure, the curve can be appropriately smoothed. For example, Origin's smoothing tool is used, the Lowess model is selected, and the span parameter is 0~0.5. Taking Example 5 as an example, the test process of the compression index is provided, such as Figure 1 , Figure 2 and Figure 3 shown.

[0057] Carbon content percentage: measured in accordance with GB / T30835-2014.

[0058] Chemical composition analysis: PE Avio200 inductively coupled plasma optical emission spectrometry (ICP-OES) was used.

[0059] Particle size: According to GB / T 19077.1, the Dv50 and Dv100 of lithium iron phosphate cathode material, as well as the Dv10, Dv50, Dv90 and broadening coefficient Span of carbon-coated lithium iron phosphate were tested using MS3000 laser particle size analyzer, where Span = (Dv90-Dv10) / Dv50.

[0060] Particle strength: Using an MCT series micro compression tester, the indenter applies a test force at a constant increasing rate to a single particle and fixes it between the flat indenter and the lower platen. The deformation of the sample is then automatically measured, and the particle is judged to have been crushed by a sudden drop in pressure. The particle strength is calculated according to the maximum pressure F before the sudden drop in pressure according to formula (1). At least 10 particles are taken from each sample for testing and the average value is calculated.

[0061] Particle strength = 2.8 × F / (πd 2 ) formula (1) F represents the maximum pressure value before the pressure drop, in mN; d represents the particle diameter, in μm.

[0062] Pole compaction density: The mass ratio of lithium iron phosphate material, binder, and conductive carbon black is 95:3:2. First, PVDF is dissolved in NMP to obtain a 5wt% binder solution, and then lithium iron phosphate material and conductive carbon black are added and stirred to obtain a slurry; a 300μm coating applicator is used to coat the slurry on an aluminum foil with a thickness of 20μm, and dried at 100℃ for 8h to control the single-sided surface density to 400±1g / m 2 ; Then the dried electrode sheet is pressed, the pressing roller temperature is 40°C, and the pressing roller applies a pressure of 6MPa to obtain the positive electrode sheet; a spiral micrometer with an accuracy of 0.5μm is used to measure the thickness of the positive electrode sheet and calculate the compaction density of the positive electrode sheet PD = the surface density of the positive electrode sheet ÷ (the thickness of the positive electrode sheet - 20μm).

[0063] Battery energy density: The prepared positive electrode sheets are assembled into laminated batteries, and the volume energy density and mass energy density of the batteries are tested. The preparation method of the negative electrode sheets is as follows: the mass ratio of graphite, conductive carbon black, CMC, and styrene-butadiene rubber is 95.5:1:1.5:2; first, CMC is dissolved in water, and then graphite and conductive carbon black are added and stirred; finally, styrene-butadiene rubber is added, vacuum stirring is completed, and the material is sieved to obtain a negative electrode slurry with a solid content of 50%. The negative electrode slurry is coated on copper foil, cold pressed, and cut to obtain a negative electrode sheet. The compacted density of the negative electrode sheet is 1.55g / cm 3The thickness of the active material layer is 110μm; the electrolyte is EC / DMC / EMC+LiPF6+additive, the LiPF6 concentration is 1M, and the diaphragm is 20μm PE ion exchange membrane; aluminum-plastic film heat sealing is used as the outer shell; the assembled battery is formed using a Lanqi charging cabinet, the conditions are: 0.1C constant current charging to 3.8V, 0.1C discharge to 2.0V; the energy density of the formed battery is tested.

[0064] Cycle capacity retention rate: Cycle 1000 times at 1C rate, the method is to use 1C constant current to charge to 3.8V and then discharge to 2.0V at 1C constant current, capacity retention rate = discharge capacity in the 1000th week ÷ discharge capacity in the first week × 100%.

[0065] TEM: A FEI Titan Cubed G2 60-300 transmission electron microscope was used.

[0066] SEM: Nova NanoSEM 450 was used. Circularity test method: The obtained SEM images were analyzed using ImageJ image analysis software, and the individual particles that could be analyzed were identified using ImageJ. Then, the projected area and circularity of each particle (C = (4 × π × A) / G) were calculated using ImageJ. 2 , wherein A is the area of ​​the projection surface, G is the perimeter of the projection surface, and C is the particle circularity), the particle circularity of the lithium iron phosphate positive electrode material of Examples 2-3, 6, 8-10 is 0.5-1.0; the Dv50 and Dv100 of the lithium iron phosphate positive electrode material are tested using a MS3000 laser particle size analyzer in accordance with GB / T19077.1, and particles with a projection area greater than or equal to 100% are screened out in the SEM image. (Dv50 / 2) 2 The particles are taken as samples, and the average circularity of the samples is calculated. The sample size is not less than 30, that is, the average circularity of the particles in the range of Dv50-Dv100 is obtained.

[0067] Table 1 Parameter test results of products provided in each embodiment

[0068] Table 2 Pole and battery performance test results

[0069] From analysis of Table 1 and Table 2, it can be seen that the lithium iron phosphate positive electrode material provided by the present invention has both high compaction density and cycle stability, and the prepared battery has both high energy density and capacity retention rate.

[0070] Example 1 This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, and the steps are as follows: (1) Lithium chloride, titanyl sulfate and hyaluronic acid are dissolved in deionized water to obtain a polymer solution containing lithium ions, anhydrous ferric phosphate is added and stirred to keep the dispersion uniform, then ethylene glycol diglycidyl ether is added, and the mixture is heated to 60° C. and stirred continuously until the viscosity is too high to be stirred, and the reaction is stopped to obtain a gel with a solid content of 48.2%.

[0071] The concentration of lithium ions in the polymer solution containing lithium ions is 0.2 M, and the mass percentage of the polymer in the polymer solution containing lithium ions is 1%. The amount of the curing agent added is 3% of the polymer (mass fraction, the same below). Anhydrous ferric phosphate and titanyl sulfate are added according to a molar ratio of the total molar amount of Fe element and Ti element to Li element of 1:1.05, and the molar ratio of Fe to Ti is 0.95:0.05.

[0072] (2) The gel is crushed by applying pressure through an 80-mesh sieve and then sent to a fluidized drying bed for drying to a constant weight to obtain a precursor.

[0073] The fluidized bed temperature was 120°C and the air flow rate was 100 mL / min.

[0074] (3) Pre-calcining the precursor in a flash dryer to obtain a pre-calcined precursor.

[0075] Among them, the inlet air temperature of the flash dryer is 500°C, the outlet air temperature is 100°C, the rotation speed is 30Hz, and the feeding frequency is 30Hz.

[0076] (4) The pre-burned precursor is calcined, crushed, and demagnetized to obtain carbon-coated lithium iron phosphate.

[0077] The calcination gas atmosphere is an inert atmosphere (nitrogen, the same below), the temperature is 650°C, and the time is 5 hours.

[0078] (5) Carbon-coated lithium iron phosphate prepared from anhydrous iron phosphate of different particle sizes is mixed and proportioned to obtain a lithium iron phosphate positive electrode material.

[0079] Table 3 Grading scheme of Example 1

[0080] Example 2 This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, and the steps are as follows: (1) Lithium hydroxide and vinyl grafted hydroxymethyl cellulose are dissolved in deionized water to obtain a polymer solution containing lithium ions. Anhydrous ferric phosphate is added and stirred to keep the dispersion uniform. Then, photoinitiator 2959 is added, and ultraviolet radiation is turned on and stirring is continued (the wavelength of ultraviolet light is 254 nm). The reaction is stopped when the viscosity is too high to be stirred, and a gel with a solid content of 30.5% is obtained.

[0081] The concentration of lithium ions in the polymer solution containing lithium ions is 0.8 M, and the mass percentage of the polymer in the polymer solution containing lithium ions is 3%. The amount of the curing agent added is 3% of the polymer. Anhydrous ferric phosphate is added according to a molar ratio of Fe element to Li element of 1:1.1.

[0082] (2) The gel is crushed by applying pressure through an 80-mesh sieve and then sent to a fluidized drying bed for drying to a constant weight to obtain a precursor.

[0083] The fluidized bed temperature was 80°C and the air flow rate was 400 mL / min.

[0084] (3) The precursor is calcined, crushed, and demagnetized to obtain carbon-coated lithium iron phosphate.

[0085] The calcination gas atmosphere is an inert atmosphere, the temperature is 550° C., and the time is 6 hours.

[0086] (4) Carbon-coated lithium iron phosphate prepared from anhydrous iron phosphate of different particle sizes is mixed and proportioned to obtain a lithium iron phosphate positive electrode material.

[0087] Table 4 Grading scheme of Example 2

[0088] Example 3 This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, and the steps are as follows: (1) Lithium acetate and agar are dissolved in 50°C deionized water to obtain a polymer solution containing lithium ions. Anhydrous ferric phosphate is added and stirred to ensure uniform dispersion. Then polyethylene glycol diglycidyl ether (Mn 500) is added and heated to 80°C while continuing to stir. The reaction is stopped when the viscosity is too high to stir. A gel with a solid content of 42.7% is obtained.

[0089] The concentration of lithium ions in the polymer solution containing lithium ions is 0.5 M, and the mass percentage of the polymer in the polymer solution containing lithium ions is 2%. The amount of the curing agent added is 2.5% of the polymer. Anhydrous ferric phosphate is added according to a molar ratio of Fe element to Li element of 1:1.01.

[0090] (2) The gel is crushed by applying pressure through an 80-mesh sieve and then sent to a fluidized drying bed for drying to a constant weight to obtain a precursor.

[0091] The fluidized bed temperature was 100°C and the air flow rate was 200 mL / min.

[0092] (3) Pre-calcining the precursor in a flash dryer to obtain a pre-calcined precursor.

[0093] Among them, the inlet air temperature of the flash dryer is 400°C, the outlet air temperature is 150°C, the rotation speed is 30Hz, and the feeding frequency is 20Hz.

[0094] (4) The pre-burned precursor is calcined, crushed, and demagnetized to obtain carbon-coated lithium iron phosphate.

[0095] The calcination gas atmosphere is an inert atmosphere, the temperature is 600° C., and the time is 3 h.

[0096] (5) Carbon-coated lithium iron phosphate prepared from anhydrous iron phosphate of different particle sizes is mixed and proportioned to obtain a lithium iron phosphate positive electrode material.

[0097] Table 5 Grading scheme of Example 3

[0098] Example 4 The difference from Example 3 is that the gel is dried by ordinary drying, that is, the gel is placed in a 100° C. forced air oven and dried to constant weight; Table 6 Grading scheme of Example 4

[0099] Example 5 The difference from Example 3 is that in step (1), the mass percentage of the polymer in the polymer solution containing lithium ions is 3%; and the amount of the curing agent added is 5% of the polymer.

[0100] Table 7 Grading scheme of Example 5

[0101] Example 6 (1) Lithium oxalate, zirconium acetate and guar gum are dissolved in deionized water at 50°C to obtain a polymer solution containing lithium ions. Anhydrous ferric phosphate is added and stirred to keep the dispersion uniform. Then, ethylene glycol diglycidyl ether is added and heated to 80°C and stirring is continued. The reaction is stopped when the viscosity is too high to be stirred, thereby obtaining a gel with a solid content of 34.9%.

[0102] Among them, the concentration of lithium ions in the polymer solution containing lithium ions is 0.5M, and the mass percentage of the polymer in the polymer solution containing lithium ions is 2%; the amount of the curing agent added is 1% of the polymer; anhydrous ferric phosphate and the dopant are added according to the molar ratio of the total molar amount of Fe element and the dopant metal element to the Li element of 1:1.1, and the molar ratio of iron to zirconium is 0.98:0.02.

[0103] (2) The gel is crushed by applying pressure through an 80-mesh sieve and then sent to a fluidized drying bed for drying to a constant weight to obtain a precursor.

[0104] The fluidized bed temperature was 100°C and the air flow rate was 200 mL / min.

[0105] (3) Pre-calcining the precursor in a flash dryer to obtain a pre-calcined precursor.

[0106] Among them, the inlet air temperature of the flash dryer is 500°C, the outlet air temperature is 150°C, the rotation speed is 10Hz, and the feeding frequency is 30Hz.

[0107] (4) The pre-burned precursor is calcined, crushed, and demagnetized to obtain carbon-coated lithium iron phosphate.

[0108] The calcination gas atmosphere is an inert atmosphere, the temperature is 550° C., and the time is 4 hours.

[0109] (5) Carbon-coated lithium iron phosphate prepared from anhydrous iron phosphate of different particle sizes is mixed and proportioned to obtain a lithium iron phosphate positive electrode material.

[0110] Table 8 Grading scheme of Example 6

[0111] Example 7 The difference from Example 3 is that in step (3), the air inlet temperature of the flash evaporator is 300°C and the air outlet temperature is 100°C.

[0112] Table 9 Grading scheme of Example 7

[0113] Example 8 The difference from Example 3 is that the amount of curing agent added in step (1) is 1% of the polymer.

[0114] Table 10 Grading scheme of Example 8

[0115] Example 9 The difference from Example 3 is that the amount of curing agent added in step (1) is 5% of the polymer.

[0116] Table 11 Grading scheme of Example 9

[0117] Example 10 The difference from Example 3 is that the flash evaporator conditions in step (3) are as follows: the inlet air temperature is 500°C, the outlet air temperature is 150°C, the rotation speed is 30 Hz, and the feed frequency is 10 Hz.

[0118] Table 12 Grading scheme of Example 10

[0119] Comparative Example 1 The difference from Example 3 is that no curing agent is added in step (1). The steps are as follows: Lithium acetate and agar were dissolved in 50° C. deionized water to obtain a polymer solution containing lithium ions, anhydrous ferric phosphate was added and stirred to keep the dispersion uniform, and the solution was heated to 80° C. and stirred continuously until the solvent was completely evaporated to obtain a precursor 1.

[0120] The concentration of lithium ions in the polymer solution containing lithium ions is 0.5 M, and the mass percentage of the polymer in the polymer solution containing lithium ions is 2%. Anhydrous ferric phosphate is added according to a molar ratio of Fe element to Li element of 1:1.01.

[0121] (2) Precursor 1 is fed into a fluidized drying bed and dried to a constant weight to obtain precursor 2.

[0122] The fluidized bed temperature was 100°C and the air flow rate was 200 mL / min.

[0123] (3) Precursor 2 is placed in a flash dryer for pre-calcination to obtain a pre-calcined precursor.

[0124] Among them, the inlet air temperature of the flash dryer is 400°C, the outlet air temperature is 150°C, the rotation speed is 30Hz, and the feeding frequency is 20Hz.

[0125] (4) The pre-burned precursor is calcined, crushed, and demagnetized to obtain carbon-coated lithium iron phosphate.

[0126] The calcination gas atmosphere is an inert atmosphere, the temperature is 600° C., and the time is 3 h.

[0127] (5) Carbon-coated lithium iron phosphate prepared from anhydrous iron phosphate of different particle sizes is mixed and proportioned to obtain a lithium iron phosphate positive electrode material.

[0128] Table 13 Grading scheme of comparative example 1

[0129] Comparative Example 2 After ball milling, anhydrous iron phosphate, lithium acetate and agar powder were mixed, and then placed in a rotary kiln for calcination at 600°C for 6 hours, and then crushed and demagnetized to obtain carbon-coated lithium iron phosphate. Anhydrous iron phosphate and lithium acetate were mixed according to a molar ratio of n(Fe):n(Li)=1:1.01. The mixing ratio of anhydrous iron phosphate, lithium acetate and agar powder was the same as that in Example 3.

[0130] Table 14 Grading scheme of comparative example 2

[0131] Comparative Example 3 Example 4 Carbon-coated lithium iron phosphate No. 1.

[0132] Performance characterization: The TEM images of the lithium iron phosphate cathode materials prepared in Comparative Example 1 and Example 3 are as follows: Figure 4 As shown, it can be seen that the lithium iron phosphate positive electrode material prepared in Example 3 has better uniformity.

[0133] The SEM image of the lithium iron phosphate positive electrode material prepared in Example 1 is as follows Figure 5 As shown, the SEM image of the lithium iron phosphate positive electrode material prepared in Example 3 is as follows Figure 6 As shown, it can be seen that the prepared lithium iron phosphate positive electrode material contains large particles and small particles, and the average circularity of the large particles (above Dv50) in Example 3 is higher than that in Example 1.

[0134] Combined with Table 1, Table 2 and the preparation method, each embodiment and comparative example are analyzed: Specifically, the compression index of Comparative Example 1 is too large, resulting in a low compaction density, a large electrode sheet resistance, and thus a low energy density. The reason is that the lack of a curing agent causes a significant decrease in the uniformity of the carbon coating layer (see TEM figure), resulting in a high compression index.

[0135] Example 1 Compression Index It satisfies 0.4-5.0, but the particle strength does not meet 40MPa-150MPa. Example 1 has higher particle strength. Compared with Example 5, the two have similar compression indexes, but since the particle strength of Example 1 is too high, its compaction density is lower. The reason is that: the particle strength of Example 5 is lower. When measuring the compaction density, the particles will be crushed to release stress and thus increase the compaction density. However, the fragmentation of the particles will cause the transmission path of electrons / ions to become longer, thereby increasing the resistance of the electrode. The fragmentation of the particles will also lead to poor cycle performance.

[0136] Example 2 Compression Index It satisfies 0.4-5.0, the particle strength satisfies 40MPa-150MPa, but does not meet 60MPa-120MPa, and the compressibility factor does not meet 120MPa-300MPa. Since Example 2 has more lithium iron phosphate with small particles, it has a lower compression index, so it has a higher compaction density, but a higher electrode resistance; in addition, the particle strength of Example 2 is lower, so the cycle capacity retention rate is lower.

[0137] Examples 3 to 5 have similar particle strengths but different compression indices. From the perspective of the percentage content of the carbon coating layer, the average circularity, and the grading scheme of the three, the difference in the compression index comes from the percentage content of the carbon coating layer and the average circularity. From the performance test, as the compression index increases, the compaction density of the powder decreases, and therefore the compaction density of the pole piece decreases; the pole piece resistance increases slightly because a certain degree of increase in carbon content is conducive to improving conductivity, but a decrease in circularity will cause an increase in particle interface resistance, so the pole piece resistance does not change much under the two forces.

[0138] Examples 3, 6, and 7 have similar compression indexes but different particle strengths. The greater the particle strength, the smaller the compaction density of the powder and the electrode, but the smaller the electrode resistance, the higher the cycle capacity retention rate; although the average circularity of Examples 6 and 7 is smaller, the grading effect is better, and the number of small-particle lithium iron phosphate is larger, so the compression index is similar to that of Example 3, indicating that the powder movement ability of the lithium iron phosphate positive electrode material can be regulated by adjusting the process parameters of the preparation method of the present invention.

[0139] The compressibility factors of Examples 3, 6, 8, and 10 satisfy 120 MPa-300 MPa. Therefore, compared with other Examples, they have the best comprehensive performance in terms of good compaction density, electrode conductivity, and capacity retention.

[0140] During the preparation of Examples 3, 8, and 9, different amounts of curing agents were added. From the results, the greater the amount of curing agent added, that is, the higher the degree of crosslinking of the gel, the greater the compression index of the obtained lithium iron phosphate positive electrode material, and the particle strength slightly increased. Further analysis shows that the circularity, carbon coating content, and grading scheme of the three are not much different; but when no curing agent is added (Comparative Example 1), the compression index of the lithium iron phosphate material is higher than that of Example 9. The reason is that when no curing agent is added, gel cannot be obtained, and the number of iron phosphate, lithium ions, and polymers contained in a unit volume cannot be fixed, so the obtained lithium iron phosphate material is severely agglomerated, so the Dv50 of the obtained lithium iron phosphate material is larger and the span is larger. In addition, from the TEM images of Example 3 and Comparative Example 1, no curing agent is added to Comparative Example 1, and the uniformity of its carbon coating layer is worse than that of Example 3, so it has a larger compression index, indicating that the addition of curing agent and its addition amount have a greater influence on the uniformity of the carbon coating layer. Not adding curing agent or excessive curing agent is not conducive to forming a uniform coating layer, which leads to an increase in the compression index.

[0141] Different flash evaporation conditions were used during the preparation of Examples 3, 7, and 10. Specifically, as the inlet air temperature during flash evaporation increased, the particle strength of the material increased and the roundness became better. However, since the grading scheme of Example 7 contained more small-particle lithium iron phosphate, Examples 3 and 7 had similar compression indexes. Since the grading scheme of Example 10 was similar to that of Example 3, Example 10 had a lower compression index due to its higher average roundness. Although its hardness was higher, its compression index was lower, so the compacted density of the powder was similar to that of Example 3.

[0142] In Comparative Example 2, the polymer and lithium salt are mixed with anhydrous iron phosphate by a solid phase method, and the compression index of the obtained lithium iron phosphate positive electrode material is relatively large, so the compaction density of the powder and the electrode sheet is relatively low, and the electrode sheet resistance is relatively high.

[0143] Compared with Example 4, Comparative Example 3 was not graded, so the compression index was relatively large.

[0144] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: The invention comprises a lithium iron phosphate active material, wherein a carbon coating layer is provided on the surface of the lithium iron phosphate active material; The average circularity of the particles of the lithium iron phosphate positive electrode material within the range of Dv50-Dv100 is greater than or equal to 0.6; The compression index of the lithium iron phosphate positive electrode material is 0.4-5.0, wherein the compression index is obtained by the following method: Obtain the density-pressure relationship curve of the lithium iron phosphate positive electrode material at different pressing speeds, perform linear fitting on the portion of the density-pressure relationship curve above 100 MPa and obtain the corresponding slope, make a relationship curve between the pressing speed and the slope, and perform linear fitting on the relationship curve between the pressing speed and the slope to obtain the slope of the fitting line as the pressing index.

2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The particle strength of the lithium iron phosphate positive electrode material is 40MPa-150MPa.

3. The lithium iron phosphate positive electrode material according to claim 2, characterized in that: The lithium iron phosphate positive electrode material satisfies at least one of the following characteristics: Feature A1: Particle strength is 60MPa-120MPa; Feature A2: The average circularity of particles in the range of Dv50-Dv100 is 0.65-0.80; Feature A3: compacted density is 1.5g / cm 3 -3.0g / cm 3 ; Feature A4: The mass proportion of the carbon coating layer in the lithium iron phosphate positive electrode material is 0.5%-5%.

4. The lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: Definition: Compressibility factor = ; The lithium iron phosphate positive electrode material meets the compressibility factor of 120MPa-300MPa.

5. A method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: include: The iron phosphate and the polymer solution containing lithium ions are mixed, and then mixed with a curing agent for curing reaction to obtain a gel; wherein the polymer solution containing lithium ions is obtained by dissolving a soluble lithium salt and a polymer in a solvent; The gel is crushed and then dried to obtain a precursor; calcining the precursor to prepare carbon-coated lithium iron phosphate; The carbon-coated lithium iron phosphate with different particle sizes is mixed.

6. The preparation method according to claim 5, characterized in that: The process of preparing the gel has at least one of the following characteristics: Feature B1: The polymer is a soluble polymer containing at least one of a hydroxyl group, a vinyl group and an epoxy group; the curing agent is selected according to the active groups contained in the polymer. When the polymer contains a hydroxyl group, the curing agent is a glycidyl ether; when the polymer contains a vinyl group, the curing agent is a soluble photoinitiator; when the polymer contains an epoxy group, the curing agent is a polyol; Feature B2: The soluble lithium salt is selected from at least one of lithium chloride, lithium hydroxide, lithium acetate and lithium oxalate; Feature B3: The solvent is selected from at least one of water, ethanol, methanol and isopropanol; Feature B4: The concentration of lithium ions in the lithium ion-containing polymer solution is 0.2M-0.8M, the mass percentage of the polymer in the lithium ion-containing polymer solution is 1%-3%, and the mass ratio of the added amount of the curing agent to the polymer is (1-5): 100; Feature B5: After mixing anhydrous ferric phosphate, a dopant and the polymer solution containing lithium ions, the mixture is mixed with a curing agent for a curing reaction, wherein the dopant is a soluble compound containing a doping element, and the doping element is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn, Y, Mg, Na, N, S and F; the molar ratio of the total molar amount of the iron element in the anhydrous ferric phosphate and the doping element to the lithium element is controlled to be 1: (1.01-1.10); Feature B6: The curing reaction is carried out by at least one of heating and stirring reaction, ultraviolet irradiation and stirring reaction, and microwave irradiation and stirring reaction; when the curing reaction is carried out by heating and stirring reaction, the reaction temperature is controlled to be 50°C-80°C; when the curing reaction is carried out by ultraviolet irradiation and stirring reaction, the light wavelength is controlled to be 200nm-400nm; when the curing reaction is carried out by microwave irradiation and stirring reaction, the microwave irradiation power is controlled to be 200W-500W; Feature B7: The solid content of the prepared gel is 30%-50%.

7. The preparation method according to claim 5, characterized in that: The gel is crushed and then fluidized drying is performed; The fluidized drying refers to placing the crushed gel in a fluidized bed for drying, controlling the drying temperature to be 80°C-120°C, and the air flow rate to be 50mL / min-400mL / min.

8. The preparation method according to claim 5, characterized in that: The process of preparing the carbon-coated lithium iron phosphate from the precursor has at least one of the following characteristics: Characteristic C1: calcination temperature is 550°C-650°C, and calcination time is 2h-6h; Characteristic C2: Calcination is carried out under an inert atmosphere; Feature C3: The precursor enters the flash dryer for preheating before calcination, and the air inlet temperature of the flash dryer is controlled to be 300°C-500°C, the air outlet temperature is 100°C-150°C, the rotation speed is 10Hz-30Hz, and the feeding frequency is 10Hz-30Hz; Feature C4: After the precursor is calcined, it is crushed and demagnetized to obtain the carbon-coated lithium iron phosphate.

9. The preparation method according to claim 5, characterized in that: The method of mixing the carbon-coated lithium iron phosphate with different particle sizes is selected from the first method or the second method; The process of using the first method to mix the two carbon-coated lithium iron phosphates with different particle size distributions is mixed in proportion, and the Dv50 of the two carbon-coated lithium iron phosphates with different particle size ranges are Dv50 and Dv50, respectively. a 、Dv50 b , where 15μm≥Dv50 a ≥2.4Dv50 b ≥1μm; with Dv50 a and Dv50 b The mass ratio of the two carbon-coated lithium iron phosphates is (20%~35%): (65%~80%); The process of using the second method to mix the three carbon-coated lithium iron phosphate particles with different particle size distributions is mixed in proportion, and the Dv50 of the three carbon-coated lithium iron phosphate particles with different particle size ranges are Dv50 and Dv50, respectively. a 、Dv50 b 、Dv50 c , where 15μm≥Dv50 a ≥2.4Dv50 b ≥2.4 2 Dv50 c ≥2μm; with Dv50 a 、Dv50 b and Dv50 c The mass ratios of the three types of carbon-coated lithium iron phosphate are (2%~20%): (40%~60%): (30%~40%).

10. A lithium battery, characterized in that: The invention comprises the lithium iron phosphate positive electrode material according to any one of claims 1 to 4 or the lithium iron phosphate positive electrode material prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Polymer-coated lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN115241462A

  • Lithium iron phosphate material and preparation method and application thereof

    CN117996073A

  • Positive electrode material and preparation method thereof, secondary battery and electric equipment

    CN118538912A

  • Composite lithium iron phosphate as well as preparation method and application thereof

    CN118658979A

  • Lithium iron phosphate precursor and preparation method thereof, lithium iron phosphate and preparation method and application thereof

    CN119018871A

Cited By

  • Battery cell, battery device, electric device, and energy storage device

    CN120300266A

  • Battery cell, battery device, power consuming device, and energy storage device

    CN120300266B

  • Battery cell, battery device, electric device, and energy storage device

    CN120300267A

  • Battery cell, battery device, power consuming device, and energy storage device

    CN120300267B

  • Battery cell, battery device, electric device, and energy storage device

    CN120300268A